Collecting Race-Based Data in Health Research: A Critical Analysis of the Ongoing Challenges and Next Steps for Canada - Sheikh, Fatima; Fox-Robichaud, Alison; Schwartz, Lisa (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2023)
The COVID-19 pandemic has had a global effect. The disproportionate impact on Indigenous peoples and racialized groups has brought ethical challenges to the forefront in research and clinical practice. In Canada, the Tri-Council Policy Statement (TCPS2), and specifically the principle of justice, emphasizes additional care for individuals “whose circumstances make them vulnerable”, including Indigenous and racialized communities. In the absence of race-based data to measure and inform health research and clinical practice, we run the risk of causing more harm and contributing to ongoing injustices. However, without an accepted framework for collecting, maintaining, and reporting race-based data in Canada, more guidance is needed on how to do this well. Importantly, a framework for collecting race-based data should build on existing guidance from Indigenous and other structurally marginalized communities, the TCPS2, recommendations from the World Health Organization, and involve relevant stakeholders. In this paper, we describe historical examples of unethical studies on Indigenous and racialized groups, discuss the challenges and potential benefits of collecting race-based data, and conclude with objectives for a pan-Canadian framework to inform how race-based data is collected, stored, and accessed in health research.